Integrative Islamic Learning Shapes Students’ Religious Attitudes in Social Studies: Pembelajaran Islam Terpadu Mempengaruhi Sikap Keagamaan Siswa dalam Mata Pelajaran Ilmu Sosial - Widianata, Risha Agustina; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Developing students’ religious attitudes is a crucial aspect of character education in primary schools, particularly in the context of Social Studies learning. Specific Background: Integrative learning based on Islamic values offers opportunities to incorporate moral and spiritual dimensions alongside cognitive and psychomotor skills. Knowledge Gap: However, limited studies examine how such integrative approaches manifest in improving students’ daily religious practices and attitudes. Aims: This study investigates how integrative Islamic-based learning in Social Studies shapes the religious attitudes of fourth-grade students. Results: Findings indicate that students exposed to integrative learning demonstrate significant improvements in cognitive understanding, affective disposition, psychomotor engagement, and the practical application of religious values in daily life. Novelty: This study highlights a comprehensive framework linking Islamic values to multiple learning domains, providing evidence beyond conventional moral education approaches. Implications: The findings suggest that embedding spiritual and moral elements within standard curricular subjects can foster holistic development, guiding educators in designing value-oriented learning activities that influence both classroom behavior and everyday practices. Highlights: Integrative learning promotes holistic development across cognitive, affective, and psychomotor domains. Practical application of religious values in daily life is enhanced. Provides a model for embedding moral-spiritual education within standard subjects. Keywords: Islamic Values, Integrative Learning, Social Studies, Religious Attitudes, Primary Education